PENGARUH CAMPURAN EKSTRAK AGLAIA HARMSIANA PERKINS DAN DYSOXYLUM ACUTANGULUM MIQ. (MELIACEAE) TERHADAP MORTALITAS DAN OVIPOSISI PLUTELLA XYLOSTELLA (L.) (LEPIDOPTERA: YPONOMEUTIDAE) - Yuswanti, Lucy; Prijono, Djoko (Universitas Lampung, 2004)
Effect of Mixture of Aglaia harmsiana Perkins and Dysoxylum acuntangum Miq. (Meliaceae) Extracts on Mortality and Oviposition of Plutella xyostella (L.) (Lepidoptera: Yponomeutidae). This study was conducted to evaluate the effect of mixture of extracts of Aglaia harmsiana seeds and Dysoxylum acutangulum leaf petioles on mortality and oviposition of Plutella xyostella (L.) (Lepidoptera: Yponomeutidae). The insecticidal activity of ethyl acetate fraction of A. harmsiana and D. Acutangulum extracts and their mixture (concentration ratio of Ah and Da was 4:1) was evaluated against the thrid-instar P. xylostella was assessed by choice tests using broccoli seddlings. LC50 and LC95 of A. harmsiana extracts against the thirds the+fourth instar larvae were 0.054% and 0.129%, respectively, those of D. acutangulum extract were 0.031% and 0.103%, and those of the the mixture of A. harmsiana and D.acutangulum extract and the mixture at concentrations of 0.06% - 0.38%, 0.3%, and 0.02% - 0.3%, respectively, significantly reduced the number of eggs deposited by the female, P. xylostella on broccoli seedings, with oviposition inhibition indices of 0.30-0.59, 0.28-0.45 and 0.045-0.70. A.harmsiana ectract at all concentrations tested was phytotoxic to broccoli seedlings, whereas D. acutangulum extract was not. Mixture of A. harmsiana and D. acutangulum extract were phytotoxic to broccoli seedlings at concentrations of 0.06-0.3%. Thus, A. hamarsiana extract of mixture containing the extract should be used with caution and their phytotoxicity should be specifically tested on target crops before being used in the field.